Assessing biochar, clinoptilolite zeolite and zeo-char loaded nano-nitrogen for boosting growth performance and biochemical ingredients of peace lily (Spathiphyllum Wallisii) plant under water shortage - Hend Mohammad Saad Ibrahim; Abdel Wahab M. Mahmoud; Marwa Mohamed Soliman; Shaimaa Mahmoud Heider; Shady Abdel Mottaleb (BMC Plant Biology, 2024)
Abstract Background Peace lily (Spathiphyllum wallisii Regel) is an ornamental indoor plant with promising cut flower market, as well as antiviral, pharmacological and ecological potentials. Water deficiency can have sound effects on the growth performance and aesthetic quality of such plant. The aim of this study was to investigate the consequences of zeolite, biochar, and zeo-char loaded nano-nitrogen application on the growth performance and biochemical components of peace lily under water shortage conditions. An experiment was conducted over two consecutive seasons (2021–2022) at the experimental nursery of Ornamental Horticulture Department, Faculty of Agriculture, Cairo University, Giza, Egypt. Soil amendments; zeolite, biochar, and zeo-char loaded nano-nitrogen were prepared and applied to soil before cultivation. Results Our results revealed that the new combination treatment (zeo-char loaded nano-N) had an exceeding significant effect on most of the studied parameters. Vegetative traits such as plant height (35.7 and 35.9%), leaf number per plant (73.3 and 52.6%), leaf area (40.2 and 36.4%), stem diameter (28.7 and 27.1%), root number (100 and 43.5%) and length (105.7 and 101.9%) per plant, and fresh weight of leaves (23.2 and 21.6%) were significantly higher than control (commercially recommended dose of NPK) with the application of zeo-char loaded nano-N during the two growing seasons, respectively. Similar significant increments were obtained for some macro- (N, P, K, Mg, Ca) and micro- (Fe, Zn, Mn) elements with the same treatment relative to control. Chlorophyll (18.4%) and total carotenoids (82.9 and 32.6%), total carbohydrates (53.3 and 37.4%), phenolics (54.4 and 86.9%), flavonoids (31.7% and 41.8%) and tannins (69.2 and 50%), in addition to the phytohormone gibberellic acid (GA3) followed the same trend with the application of zeo-char loaded nano-N, increasing significantly over control. Leaf histological parameters and anatomical structure were enhanced with the new combination treatment in comparison with control. Antioxidant enzymes (catalase and peroxidase), proline and abscisic acid (ABA) exhibited significant declines with zeo-char loaded nano-N treatment relative to control. Conclusion These findings suggest that incorporating soil amendments with nano- nutrients could provide a promising approach towards improving growth performance and quality of ornamental, medicinal and aromatic species under water deficiency conditions.